Rural Pupils Making their Way through the Norwegian Education System: Enablements, Constraints and Agency in a Northern Norwegian Context - Stenseth, Anna-Maria (UiT Norges arktiske universitet, 2022)
This thesis focuses on pupils’ agency and their experiences with and reflections on educational choices. The theoretical framework draws on Margaret Archer’s morphogenetic approach as it examines parts of the educational situational logics, as well as her Three-Stage Model in which structural and cultural properties shape agents’ situations. The thesis thus explores constraints and enablements pupils face, and courses of actions that are produced through their reflexive deliberations. The thesis is based on semistructured interviews at two points in time with eighteen pupils in one rural and one urban municipality; it is supplemented by the researcher’s previous experiences and contextual knowledge. This thesis argues that rural pupils are constrained by rural demography, the centralized education system, the assimilation/colonisation of the Sámi people and a spatially and ethnically unaware curriculum. Local opportunities’ structures, to some extent, enable rural pupils. In addition, their decision-making capabilities enable them to navigate within existing structures. In Archer’s theory, spatial contexts are not entirely explicit; the way spatial constraints and enablements are actualised in specific structural contexts can be further developed. Theoretically, this thesis engages with spatial contexts in addressing structural constraints and enablements. It emphasises space within Archer’s theoretical framework, as spatial properties produce unequal conditions for education. Avhandlinga setter søkelys på elevers aktørskap og deres erfaringer med, og refleksjoner omkring valg av utdanning. Det teoretiske rammeverket bygger på Margaret Archers morfogenetiske tilnærming. Rammeverket benyttes for å undersøke enkelte aspekter ved utdanningens situasjonslogikk. I tillegg gjøres det bruk av Archers Trestegs-modell som muliggjør en analyse av hvordan strukturelle og kulturelle egenskaper påvirker situasjonen til aktører. Avhandlinga undersøker dermed hvordan elevene refleksivt overveier egne handlinger i lys av ...